Técnica de energía muscular en pacientes adultos con cervicalgia - García Timias, Shirley Wendy (2025)
Cervicalgia, a type of neck pain affecting a large portion of the population, particularly working-age adults, is associated with disorders of the cervical spine, a structure highly susceptible to injury. Muscle energy techniques focus on controlled muscle activation with the aim of reducing pain and improving mobility. These techniques encourage the patient’s active participation in their recovery process. Objective: To analyze the effects of muscle energy techniques on clinical outcomes in adult patients with cervicalgia. Methodology: A documentary and bibliographic study was conducted, focusing on the analysis of existing literature regarding the application of muscle energy techniques in patients with cervicalgia. An inductive and descriptive approach was adopted, based on studies published between 2014 and 2024. A total of 26 articles were selected from databases such as Web of Science, Scopus, and Medline, using specific keywords and Boolean operators. Results: After applying inclusion and exclusion criteria, 26 scientific articles were selected: 13 reported a significant reduction in pain; 5 showed improvements in range of motion (ROM); 4 indicated benefits in functional performance; and 4 showed no significant differences in the evaluated variables. Conclusion: Muscle energy techniques have proven effective in the recovery of adult patients with cervicalgia, as they offer a non-invasive approach that promotes patient autonomy and significantly contributes to pain reduction and improved functionality.